Acts of Violence against Children Outside the Investigation Process by Police Officers - Ulil Amri; Iskandar, Ismail; Muh Abi Dzarr Al-Ghiffariy (Fakultas Hukum Universitas Widya Mataram, 2024)
Reports from legal aid organizations show signs of physical violence which should be a major concern in the investigation, but these appear to be ignored in the authorities' official reports. The research aims to examine the procedural law violations committed by police officers in cases of violence against children outside the investigation process. This study uses a normative juridical approach with an analysis of the murder case of Afif Maulana as the main illustration. The results show several serious violations of legal procedures that negatively impact the transparency and accountability of investigations. Violence by police officers against children also violates various national and international regulations on child protection. These violations significantly affect the psychological condition of children and cause deep trauma. This research emphasizes the importance of reforming Indonesia's judicial and law enforcement systems to ensure better protection for children in conflict with the law. Keywords: Violence; children; investigation; police